Analysis of the flora of railways of Kharkov - Звягінцева, К. О. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 2013)
Original materials of field research are given, as well as data from herbaria of M.G.Kholodny Institute of Botany, NAS of Ukraine (KW) and V.N.Karazin Kharkiv National University (CWU). Species composition of the flora of railways of Kharkov is presented by 269 species of vascular plants, 166 genera and 50 families. In the course of structural and fractional analysis peculiarities of the flora of railways of Kharkov have been elucidated.